Replacement of conventional plastic shampoo packaging for biodegradable ones – a survey. - Saboia, Laís da Costa; Oliveira, Renata Nunes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Packaging is present in our daily lives, however, packaging for cosmetics is based on polymers from petroleum, which cause environmental impacts. A promising alternative would be the usage of biodegradable materials, such as biopolymers packaging. The present work proposed a survey to map public opinion about hygienic products change. 151 people from different segments of society answered the survey (questions related to environmental awareness, possible acceptability of changing traditional shampoos packaging for biodegradable ones). It was also observed the influence of the level of education on these choices. A large part of the participants was willing to accept products encased in biodegradable materials, but these group of people would have caution due to probable increase of price. In addition, there is a correlation between level of education and the attitude towards the environmental perspective, so those who studied more, tend to have more positive attitudes towards the environment